Comparative Analysis of Islamic Family Law and Normative Law: Examining the Causes of Divorce in Purwokerto, Indonesia - Nafisah, Durotun; Nasrudin, Nasrudin; Meidina, Ahmad Rezy; Zain, Muhammad Fuad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The elevated divorce rate in Purwokerto has become a focal point for the local government due to its adverse repercussions. This research has identified five primary factors contributing to divorce, encompassing education, economic status, religion, access to healthcare, and environmental factors. This study employs empirical legal methods analyzed in accordance with Islamic family law theory. In-depth interviews were conducted with informants, as well as literature studies and data collection techniques. The results showed two critical findings. First, Islamic family law makes it clear that although divorce is legal, God views it negatively. Divorce is considered a final option when mediation becomes unfeasible. For a divorce to be valid, it must meet various criteria, such as guidelines for property division and child custody. Additionally, the Qur'an and Hadith discuss the five legitimate reasons for divorce. Secondly, the issue of divorce is regulated by normative positive law. However, no legal regulations are specifically available at the local government level to support efforts to reduce divorce rates based on the five leading causes. In particular, the five causes of divorce are also discussed based on relevant normative regulations and support from previous studies. The two sources of family law and Islamic law have different views regarding the legal requirements of divorce and its scope. However, in terms of similarities, both sources of family law and Islamic law support efforts to protect children and empower women victims of divorce. With national legal regulations, the government is responsible for providing effective rules to resolve the causes of high divorce rates legally.